Ubiquitous and context-aware computing modelling : study of devices integration in their environment - Gregório, Francisco José de Vilhena Leitão (2018)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Information Systems and Technologies Management